Recent advances in nanoparticle applications in respiratory disorders: a review - Taghavizadeh Yazdi, Mohammad Ehsan; Qayoomian, Mohsen; Beigoli, Sima; Boskabady, Mohammad Hossein (Frontiers in Pharmacology, 2023)
Various nanoparticles are used in the discovery of new nanomedicine to overcome the shortages of conventional drugs. Therefore, an updated and general review on the effects of nano-based drugs that were used in treating respiratory disorders based on basic and clinical studies was presented. Databases of PubMed, Web of Knowledge and Scopus were searched until the end of August 2022 regarding the effect of nanoparticles on respiratory diseases. Nanomedicine as a new tool provided promising applications on pulmonary diseases. The basic composition and intrinsic characteristics of nanomaterials showed their effectiveness in treating pulmonary diseases. The efficiency of various nanomedicines was demonstrated in experimental animal models of asthma, chronic obstructive pulmonary disease (COPD), pulmonary fibrosis, lung cancer, lung infection and other lung disorders, confirming their function in the improvement of respiratory disorders. Various nanomaterials such as carbon nanotubes, dendrimers, polymeric nanomaterials, liposomes, quantum dots, metal and metal oxide nanoparticles showed therapeutic effects on respiratory disorders, which may lead to new possible remedies for various respiratory illness that could increase drug efficacy and decrease side effects.